Influence of an Unstable Hydro Regime of Reservoir Bodies of The South Aral Region on the Species Diversity of Higher Aquatic Vegetation - Askar Bekbaulievich Bektursynov (Scientific Trends, 2024)
The species diversity of the hydrophilic flora of reservoirs located within the Southern Aral Sea region was studied: Muynak Bay, Sarbas, Shegekul, Koksu, the dynamics of higher aquatic vegetation in conditions of unstable hydraulic regime in the period 2009-2023. The overgrowth of reservoirs under conditions of unstable hydraulic regime was studied.
Keywords: Southern Aral Sea region, Muynak Bay, Sarbas, Shegekul, hydroregime, higher aquatic vegetation, water milfoil, pondweed.